2021
DOI: 10.1080/21655979.2021.1956247
|View full text |Cite
|
Sign up to set email alerts
|

Identification of four gastric cancer subtypes based on genetic analysis of cholesterogenic and glycolytic pathways

Abstract: Warburg phenomenon refers to the development of unique metabolic patterns during the growth of tumor cells. This study stratified gastric cancer into prognostic metabolic subgroups according to changes in gene expressions related to glycolysis and cholesterol synthesis. The RNA-seq expression data, single nucleotide variants (SNV), short insertions and deletions (InDel) mutation data, copy number variation (CNV) data and clinical follow-up information data of gastric cancer tissues were downloaded from The Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Previous research has revealed that metabolic grouping is associated with clinical and mutational profiles in multiple cancer types ( 20 , 21 ). We therefore sought to characterize the clinical relevance of the previously described metabolic subtypes in EGFR-WT NSCLC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has revealed that metabolic grouping is associated with clinical and mutational profiles in multiple cancer types ( 20 , 21 ). We therefore sought to characterize the clinical relevance of the previously described metabolic subtypes in EGFR-WT NSCLC.…”
Section: Resultsmentioning
confidence: 99%
“…Karasinska et al constructed a stratification framework for pancreatic cancer based on the glycolytic/cholesterol cluster and found that patients with glycolytic tumors were associated with a worse prognosis in both resectable and metastatic pancreatic cancer ( 39 ). The stratification framework was also applied in other cancer types, but different correlations between metabolic subtypes and prognosis were observed in various cancer types ( 20 , 21 ). These studies reveal that glycolytic/cholesterol metabolic processes play different functional roles in oncogenesis and cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the mRNA expression values of the 26 HRGs, the samples were clustered by the “ ConsensusClusterPlus ” package of the R software [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The abnormal expression of TP53 and MYC may facilitate the malignant progression of gastric cancer by facilitating cholesterol synthesis and affecting the use of cholesterol. From the genotyping of the metabolic genes of gastric cancer, differences may exist in patients subjected to different metabolic subtypes of gastric cancer in clinical characteristics (e.g., survival), and a clinically feasible gastric cancer grading scheme can be developed to guide the design of gastric cancer targeted therapy ( 74 ).…”
Section: Different Gastric Cancer Types Are Heterogenous In Terms Of ...mentioning
confidence: 99%